The Effect of Career Development and Self-Esteem on the Job Satisfaction of Civil Servants at the Office of the Ministry of Religious Affairs of Pontianak - Tassyia Nurdea; Irfan Mahdi (Universitas KH. Abdul Chalim Mojokerto, 2026)
The development of Society 5.0 positions human resources as a strategic factor in achieving organizational goals, including in government institutions that deliver public services. The job satisfaction of Civil Servants (ASN) has become an important issue because it is associated with productivity, discipline, and service quality. Empirical data at the Office of the Ministry of Religious Affairs of Pontianak City for the period 2022–2024 indicate fluctuations in absenteeism, lateness, as well as a significant decline in promotions, which suggests the need to examine factors that influence job satisfaction. The research problem in this study is whether career development and self-esteem affect the job satisfaction of ASN at the Office of the Ministry of Religious Affairs of Pontianak City, both partially and simultaneously. This study aims to analyze the effect of career development and self-esteem on ASN job satisfaction based on empirical conditions during the period 2022–2024. The research method uses a quantitative approach with multiple linear regression analysis involving 92 ASN respondents. Instrument testing was conducted through validity and reliability tests, as well as classical assumption tests including normality, linearity, and multicollinearity. The results show that career development has a positive and significant effect on job satisfaction, self-esteem has a positive and significant effect on job satisfaction, and both variables simultaneously have a significant effect with a coefficient of determination of 74.8%. This study indicates that ASN job satisfaction is formed through the interaction of organizational structural factors and individual psychological factors, which has implications for career management and strengthening employees’ psychological conditions in the public bureaucratic environment.